JOB SATISFACTION, COMPENSATION AND ORGANIZATIONAL COMMITMENT AS ANTECEDENTS OF TURNOVER INTENTION - Ricky Mual; Novalien Lewaherilla; Ferdy Leuhery (SEAN Institute, 2023)
This study aims to determine the effect of Job Satisfaction, Compensation and Organizational Commitment on Turnover Intention (Study at PT Bank Danamon Indonesia Ambon Branch). Respondents in this study were Bank Danamon Ambon Branch employees with a sample of 34 respondents. This type of research is associative and the data source uses primary data. Data collection techniques using questionnaires through manual questionnaires. The collected data were then analyzed using SPSS software. The results showed that Job Satisfaction has a significant effect on Turnover Intention then Compensation has a significant effect on Turnover Intention. However, other findings state that Organizational Commitment has a significant effect on Turnover Intention. Then the limitations in this study were that the respondents who were involved were only employees of the Ambon Branch of Bank Danamon. For this reason, it is hoped that further research can add other variables and add respondents from other banks.